Armonización fiscal en el Mercosur: Aspectos tributarios e incentivos - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2005)
– In an integration process, the quality of the agreement reached depends on the affinity observed in the domestic strategies and policies. Insofar as they are compatible, the agreement will be successful. Therefore, the harmonization of policies in regional integration agreements is justified. Within the broad spectrum of public policies, fiscal policy is essential and is a powerful element that, if not properly managed, may cause serious problems in the development of regional integration agreements. In a framework of fiscal interdependence, both domestic and external variables have an influence. Internally, the level and distribution of a country's spending have significant influence on the partner, in the same way as taxes do. The symmetry observed with respect to expenditure and taxes is shown, for instance, by the fact that a subsidy to an enterprise may be granted directly (expense) or by reducing its costs (tax exemption). Although both sides of the fiscal sphere have the same effect, tax reduction does not seem to be so frowned upon by academic circles as direct subsidies. The closest case (in geographical and temporal terms) is that of the fiscal benefits granted by Brazil, which meant the relocation of investments from Argentina. As regards external variables, although capital flows are not exclusively a part of fiscal policy, to a great extent, they are the other face of it. When faced with the structural existence of fiscal deficits (in which expenditures and taxes are primary determinants) or current account deficits (tax policy being a central element of competitiveness), the economy becomes highly dependent on external saving. This study focuses on domestic variables and their effects are evaluated both from a theoretical as well as empirical perspective.
Keywords: 330; Steuerharmonisierung; MERCOSUR-Staaten